2020
DOI: 10.23822/eurannaci.1764-1489.135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of Skin Prick and ISAC Tests in the Diagnosis of Allergy

Abstract: The recent European Union and Italian regulations in the matter of in vivo test could strongly impact on current diagnostic approach, increasing the usage of in vitro tests in daily clinical practice. We evaluated 506 patients with both skin prick test and a microarray system (ImmunoCAP ISAC 112). The overall evaluation between ImmunoCAP® ISAC vs SPT showed a moderate agreement (k=0.509, 95% C.I. 0.480-0.540, SE: 0.016) considering both aeroallergens and food allergens. When we considered the concordant result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Comparison of the molecular test results with SPT results confirmed that for most PFS allergens a positive SPT correlates with sIgE detected in ISAC and/or ALEX 2 , which was not the case in a previous study comparing SPT test results with sIgE levels detected by ISAC. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the molecular test results with SPT results confirmed that for most PFS allergens a positive SPT correlates with sIgE detected in ISAC and/or ALEX 2 , which was not the case in a previous study comparing SPT test results with sIgE levels detected by ISAC. 26 …”
Section: Discussionmentioning
confidence: 99%
“…We confirmed once more that the diagnostics with both extracts and the currently available molecules are inadequate to detect properly patients hypersensitive to crustaceans and mollusks. 15 We observed a great heterogeneity of results from one patient to another using the routine diagnostic approaches, including SPT with commercial extracts, PTP with fresh material, and specific IgE measurements. We previously showed the unreliability of commercial extracts for SPT available on the market due to differences in allergenic protein concentrations, thus potentially leading to confounding results.…”
Section: Key Resultsmentioning
confidence: 97%
“…19 In addition, geographical differences could also underlie different sensitization mechanisms according to different environmental exposure. 15 Furthermore, possible occupational exposure should be considered. 20,21 These points need to be addressed in future studies.…”
Section: Key Resultsmentioning
confidence: 99%
“…In another much smaller study from Italy, SPTs were compared with the ISAC112 platform from the same manufacturer as in our study using a different technical platform but the same molecular allergens. 23 The patients differed from our study as the Italian cohort also contained a lot of food allergic and urticaria patients that had been excluded in our study focusing on inhalant allergy. Also, Der p23 was missing in their 2019 version of the ISAC.…”
Section: Discussionmentioning
confidence: 99%